Fagopyrum longistylum (Polygonaceae), a new species from Sichuan, China - Zhang, Kaixuan; Fan, Yu; Weng, Wenfeng; Tang, Yu; Zhou, Meiliang (Phytotaxa, 2021)
A new species of Fagopyrum (Polygonaceae), Fagopyrum longistylum, is described and illustrated from Huili County, Sichuan Province, China on the basis of morphological, caryological, and molecular data. F. longistylum is morphologically similar to F. gracilipes from which it differs in having green stem and short-styled flowers with long anther but it is self-compatible. In addition, F. longistylum is a diploid species with 2n=2x=16 while F. gracilipes is tetraploid with 4n=4x=32. Molecular data based on nucleotide sequence polymorphisms of internal transcribed spacers (ITSs) and the maturase K (matK) gene confirm the separation of the new species.